Optimization of pumping efficiency and divertor operation in DEMO. (August 2017) - Varoutis, S.; Bonelli, F.; Day, Chr.; Igitkhanov, Yu
Highlights: A numerical investigation using the DSMC algorithm is performed for highlighting the influence of the pumping port and the existence of the dome on the overall pumping efficiency of a DEMO divertor. The position of the pumping port directly under the dome appears to provide the highest pumping efficiency. The divertor dome enables the compression of the neutral gas. The dome has no direct influence on the macroscopic parameters at the pumping port. It is shown that without the dome, a strong outflux of neutrals towards the x-point occurs. Abstract: In the present work a sensitivity analysis of the pumping performance of a standard divertor design for two extreme dome cases (with and without) and different pumping port locations is performed. Such an investigation re-assesses the role of the divertor dome in the design of a DEMO divertor cassette. The non-linear neutral gas flow in the private flux and sub-divertor region is modeled based on the Direct Simulation Monte Carlo (DSMC) method, which takes into account the intermolecular collisions as well as the interaction of the molecules with the stationary walls. For this specific configuration, three different pumping port locations, namely in the low and high field bottom sides of the sub-divertor and directly under the dome haven been chosen. It is shown that the optimum pumping port location is found to be directly under the dome, since the pumped particle flux is increased by a factor 2–3 compared to the one, where the port is located inside the low and high field side divertor "shoulders", respectively. In addition, the divertor dome physically restricts the conductance between the private flux region and the main chamber, enabling the compression of the neutral gas. However, the dome has no direct influence on the macroscopic parameters as the number density and the temperature at the pumping port. Furthermore, it is shown that without the dome, a strong outflux of neutrals towards the plasma core and through the x-point and its vicinity can be expected. This outflux can be reduced by a factor of 2 by positioning the pumping port directly under the dome. Finally it is noted that in all the obtained calculations, the flow field remains homogeneous without the presence of vortices. This can be explained by the fact that the studied geometry does not include any high curvature surfaces, which promote the formation of such flow structures.